Pembentukan Karakter Religius Melalui Pembiasaan Shalat Dhuha Berjamaah di SMK Batik 1 Surakarta - Rishmawati, Berliana Wahyu; Permatasari, Afifah Rani; Fauziyah, Nur (Papanda Publisher, 2025)
Through the habit of praying Duha in the congregation, Batik 1 Surakarta Vocational School expects its students to have a good religious character, be more obedient to religion, and be disciplined in activities. This article will explain how the importance of character education can go beyond academic education. The recent decline in moral values has become one of the reasons for the importance of character education in schools. Schools, in this case, Batik 1 Surakarta Vocational School play an important role in shaping the character of their students by instilling religious values that increase spiritual awareness. The instilling can be done in various ways, one of which is through habituation, through repeated activities students will feel used to doing something. If something is good, they will apply that good thing in their daily lives, one example is the Duha prayer. This study uses qualitative methods of observation and interviews to determine the effect of the habit of praying Duha prayer in shaping the religious character of students.